Perancangan User Interface Berbasis Website Dalam Melihat Penjualan Produk Pada Departemen Pospaid Management - Syifa Tanjung, Lailatul; Kumala Sari, Resy; Rusnedy, Hidayati (Journal of Engineering Science and Technology Management (JES-TM), 2023)
This research aims to design a website-based User Interface that will be used to view product sales in the Postpaid Management Department. This research is important because a good User Interface can increase user efficiency in accessing and managing product sales data, which in turn can improve department performance. The research methodology used in this research is user needs analysis, User Interface prototype development, prototype testing, and user evaluation. Product sales data from the Postpaid Management Department will be used as a data source in developing the User Interface. The research results show that the User Interface design meets user needs and allows users to easily view product sales data. This User Interface provides various features that allow users to search, filter data, and view sales reports with various parameters that can be adjusted. Users also provide positive feedback regarding the ease of use of the designed User Interface. This research makes a positive contribution to the Postpaid Management Department by providing a more efficient tool in viewing product sales. The results of this research can also be a basis for further development in improving the User Interface and its functionality in accordance with the development of departmental needs.